Interfacial Tension of Toluene + Water + Sodium Dodecyl Sulfate from (20 to 50) °C and pH between 4 and 9 - Saien, Javad; Akbari, Somayeh (Journal of chemical and engineering data, 2006)
Interfacial tension of toluene + water + sodium dodecyl sulfate is reported over the aqueous surfactant concentration range of (0 to 34.68 × 10-5) mol·L-1, the temperature range of (20 to 50) °C, and the pH range of 4 to 9. This system is frequently used as a high interfacial tension system for liquid−liquid extraction investigations. The measurements were made by the drop-weight method, and interfacial tension values ranged from (23.1 to 38.1) mN·m-1. The data show a nonlinear decrease with increasing surfactant concentration and temperature; however, there is almost a linear decrease with increasing pH. The interfacial pressure is also derived. The obtained data were correlated by empirical equations.